Factors Encouraging and Discouraging Arabic Learning Motivation at Ma'had al-Jami'ah - Siti umi Aimanah; Apri Wardana; Aulia Mustika Ilmiani (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2025)
This study aims to identify factors that influence students' interest in choosing Arabic as a major at Ma'had Al-Jami'ah UIN Palangka Raya. This study was conducted to understand various aspects that encourage or hinder Arabic language learning. The research method used was a case study with interview and observation techniques. The results of the study show that teaching quality, social support, and the availability of adequate facilities are the main factors that increase learning interest, while monotonous teaching methods, time constraints, and a lack of social support are the main obstacles. These findings are expected to provide input for the Ma'had and other educational institutions in creating a learning environment that is more supportive of developing an interest in Arabic